1989
DOI: 10.1097/00000658-198902000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Occlusions for Liver Resections

Abstract: The intra- and early postoperative courses of 142 consecutive patients who underwent liver resections using vascular occlusions to reduce bleeding were reviewed. In 127 patients, the remnant liver parenchyma was normal, and 15 patients had liver cirrhosis. Eighty-five patients underwent major liver resections: right, extended right, or left lobectomies. Portal triad clamping (PTC) was used alone in 107 cases. Complete hepatic vascular exclusion (HVE) combining PTC and occlusion of the inferior vena cava below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(67 citation statements)
references
References 17 publications
2
62
0
3
Order By: Relevance
“…It is uncertain what the limits of ischemia are in the normal human liver. Several studies have shown that the liver tolerates periods of normothermic ischemia up to 90–120 min, in normal livers as well as in cirrhotic livers [41,56,57,58]. Although the human liver might tolerate ischemia better than excessive blood loss, the adverse effects of ischemia should not be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain what the limits of ischemia are in the normal human liver. Several studies have shown that the liver tolerates periods of normothermic ischemia up to 90–120 min, in normal livers as well as in cirrhotic livers [41,56,57,58]. Although the human liver might tolerate ischemia better than excessive blood loss, the adverse effects of ischemia should not be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…7 Various surgical techniques have been used to increase the percentage of resectable tumors: profound hypothermia and circulatory arrest, 8 hemodilutional anesthesia, 9 total hepatic vascular exclusion, 10 and concomitant liver and inferior vena cava resection. 11 However, none of these techniques have reliably increased the number of liver tumors amenable to partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Seguiram-se a este, vários autores que descreveram a mesma técnica sem pinçamento da aorta Offenstadt et al, 1978;Shaw et al, 1984;Delva et al, 1984Delva et al, , 1987bDelva et al, e 1989Bismuth et al, 1989;Emre et al, 1993;Berney et al, 1998).…”
Section: Exclusão Vascular Do Fígado (Evf)unclassified